Biofuels: The Devil in the Details - Fluck, Werner Thomas (2010)
In a recent Viewpoint on biofuels (BioScience 59: 926–927), Tom Simpson addressed important shortcomings of corn ethanol production: low net energy gain, competition with food production, and the loss of nitrogen from fertilizers and its environmental consequences. Simpson proposed an agricultural landscape that could produce food, feed, and fuel while improving water, air, and habitat quality by relying more on perennial biomass. However, other environmental problems are related not only to ethanol production but also apply to production of perennial biomass. Here I analyze some of the shortcomings of perennial biomass as a provider of biofuels.